Strengthening Students’ English Reading Skills and Motivation Through Flipped Classroom Strategy Using Whatsapp (WA) as a Learning Media - Sungkur, Sensianus; Ardiasih, Lidwina Sri; Saehu, Andang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study employs a quasi-experimental design to explore the effectiveness of the Flipped Classroom strategy in enhancing students' reading skills and motivation using the WhatsApp platform. The quasi-experimental technique measures the measurement results before and after treatment. In addition, this study also seeks a correlation between reading skills and reading motivation. The research participants were seventh graders of a Junior High School in Tana Tidung who were randomly selected into experimental and control classes. The instruments used in this study were a pre-post reading skills test and a pre-post reading motivation questionnaire on two dimensions, namely intrinsic and extrinsic. Both instruments have been tested for validity and reliability before being used in the study. The results showed that the significant value (2 tailed) or (P) of the post-class reading comprehension test obtained by the experimental and control classes was 0.001, which is smaller than 0.05. It is confirmed that there is a significant difference and the quality of the experimental class' results in reading comprehension, which is higher than the control class. Thus, the Flipped Classroom strategy has an impact on improving reading skills. All significant values (2 tailed) or (P) of the post-reading motivation questionnaire in both dimensions obtained by the experimental and control classes also showed significant difference as they reached 0.001, which is smaller than 0.05. In addition, the quality of the experimental class' reading motivation results were higher than the control class. Thus, the Flipped Classroom strategy has a good impact on increasing reading motivation. Meanwhile, the significance values of the Pearson correlation of the post-reading skill test and the post-reading motivation questionnaire in both dimensions obtained by the experimental class are 0.882, 0.629, and 0.522. The control class obtained 0.286, 0.151, and 0.069. These values are more than 0.05. Thus, this shows that students' reading skills are not correlated with reading motivation in the control class. So, it can be concluded that the Flipped Classroom strategy is very appropriate for improving reading skills and reading motivation using WhatsApp platform, but there is no relationship between reading skills and reading motivation. Keywords: Flipped Classroom Strategy, Reading Motivation, Reading Skill, WhatsApp.